Effect of Prostaglandin-Pregnent Mare Serum Gonadotropin Combination for Enhancing Prolificasy in Malabari Goats - Senthilkumar P (Department of Animal Reproduction, College of Veterinary and animal Sciences, 2002)
The object of present Investigation was to evaluate the efficacy of prostaglandin-PMSG combination treatment at different dose levels in order to enhance the fertility and prolificacy of Malabari does. The material used for the study consisted of 48 cycling nulliparous Malabari does of eight to ten months age and body weight 18 to 20 kg, belonging to Kerala Agricultural University Goat farm, Mannuthy. All the experimental does were administered with two doses of cloprostenol (SYNCHROMATE) at the rate of O.Sml intramuscularly 11 days apart. One day prior to the second prostaglandin administration the does were randomly divided into four groups viz. Group I, Il, III and IV with 12 in each group. On the same day group I, 11 and III were administered PMSG (FOLLIGON) intramuscularly at the rate of 200, 400 and 600 IU respectively. Group IV was maintained as control with the prostaglandin treatment alone. After the second dose of prostaglandin all does in group I, 11 and III (100%) showed oestrus and in group IV only 11 does (91.67%) exhibited oestrus. The mean time taken for onset of oestrus in group I, Il, III and IV was 28.00±2.70, 30.00±4.31, 24.00, 43.64±4.36 h respectively. Group IV was significantly different from prostaglandin-PMSG group I, II and III (P < 0.01). The mean duration of oestrus in group I, 11, III and IV was 84.00±6.94, 64.00±7.44, 86.00±7.S2 and 34.91±4.97 h respectively. Group IV was significantly different from group I, Il andIlI (P<O.Ol).